A path dependent stress-strain model for concrete-filled-steel-tube column. (15th May 2020) - Lai, M.H.; Song, W.; Ou, X.L.; Chen, M.T.; Wang, Q.; Ho, J.C.M.
Highlight: A stress-path dependent axial load-strain model of CFST column is proposed. The effect of confining stress path dependence is studied. The effects of steel-concrete interface de-bonding on confining stress and strength of CFST column are investigated. The model was verified by 177 test results of CFST columns obtained by the authors and other researchers. Abstract: High-strength concrete (HSC) has higher strength-to-weight ratio and stiffness than normal-strength concrete (NSC), which can decrease the size and embodied carbon of columns in tall buildings. Because of the brittleness of HSC, the practical design strength limit of HSC is usually limited for providing minimum ductility. One feasible way to extend this limit would be to use concrete-filled-steel-tube (CFST) column, which has a better strength-ductility performance. There are two shortcomings in theoretical models predicting the stress-strain behaviour of CFST column: (1) Most of the models did not consider the imperfect steel-concrete interface bonding due to their different dilations under axial compression; (2) A stress-path independent confining stress-strain relationship was adopted, which ignored the progressive development of tensile splitting cracks in concrete leading to a more gradual building up of confining stress under passive confinement than active pressure. Herein, to better understand and simulate the behaviour of CFST column, a theoretical stress-strain model, which consists of the following four main components, has been developed: (1) Interaction between steel tube and concrete taken into account the de-bonding effect; (2) An accurate hoop strain equation; (3) A passively confined concrete model considering stress-path dependence; (4) A three-dimensional stress-strain model for steel tube. Comparing with the measured load-strain curves obtained by the authors and other researchers, the accuracy of the proposed model in predicting the axial behaviour of CFST columns has been verified.